PENGELOLAAN FASILITAS DI OBJEK WISATA TELUK JERING KABUPATEN KAMPAR PROVINSI RIAU - Fina Novita; Siti Sofro Sidiq (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Management means a process, method, manager's actions, the process of carrying out certain activities by mobilizing other people's energy, a process that provides supervision on all things involved in implementing policies and achieving goals. This study aims to see how the condition of facilities at Teluk Jering tourism object, Kampar Regency, Riau Province and to see what efforts are made by the manager in managing facilities at Teluk Jering tourism object, Kampar Regency, Riau Province. In this study, the authors used qualitative methods as a procedure for processing data. The data collection techniques used were observation, interviews and documentation of the Head of the Management, the Managing Secretary and visitors. After conducting interviews with the informants, the authors concluded that the overall facilities for the Teluk Jering tourist attraction have been well managed, but there is a lack of facilities, namely the unavailability of souvenir shopping facilities for tourists. Keywords: management, facilities, tourism, Teluk Jering.